Domestic and foreign demand for euro banknotes issued in Germany - Nikolaus Bartzsch; Matthias Uhl (Deutsche Bundesbank, 2017)
To facilitate a more detailed study of the volume of euro banknotes in circulation issued by the Deutsche Bundesbank, it is broken down into the components of foreign demand, domestic hoarding and domestic transaction balances. These banknote demand components are estimated using the direct approach “net shipments and foreign travel” as well as an indirect approach known as the “seasonal method”. According to the new estimates, which are based on a combination of the two approaches, around 65% to 70% of the arithmetical volume of euro banknotes issued by the Bundesbank were in circulation outside Germany at the end of 2015; of this figure, 40 to 50 percentage points were in circulation outside the euro area, and 20 to 30 percentage points in other euro-area countries. Between 30% and 35% of the Bundesbank's cumulated net issuance was in circulation in Germany, of which 25 percentage points were hoarded and 5 to 10 percentage points held for transaction purposes. The newly estimated time series for domestic hoardings does not feature a noticeable break due to the euro area's low-interest-rate environment; instead, Bundesbank-issued euro banknotes may be circulating in other euro-area countries in greater numbers.
Keywords: E41; E58; 330; Euro banknote demand; foreign demand; transaction balances; hoardings